Where does Arctic beach debris come from? Analyzing debris composition and provenance on Svalbard aided by citizen scientists - Meyer, Anna Natalie; Lutz, Birgit; Bergmann, Melanie (Frontiers in Marine Science, 2023)
Plastic debris is ubiquitous in all ecosystems and has even reached locations that humans will hardly reach such as the deep ocean floor and the atmosphere. Research has highlighted that plastic debris is now pervasive even in remote Arctic regions. While modeling projections indicated local sources and long-distance transport as causes, empirical data about its origin and sources are scarce. Data collected by citizen scientists can increase the scale of observations, especially in such remote regions. Here, we report abundance and composition data of marine debris collected by citizen scientists on 14 remote Arctic beaches on the Spitsbergen archipelago. In addition, citizen scientists collected three large, industrial sized canvas bags (hereafter: big packs), filled with beached debris, of which composition, sources and origin were determined. A total debris mass of 1,620 kg was collected on about 38,000 m2 (total mean = 41.83 g m-2, SEM = ± 31.62). In terms of abundance, 23,000 pieces of debris were collected on 25,500 m2 (total mean = 0.37 items of debris m-2, SEM = ± 0.17). Although most items were plastic in both abundance and mass, fisheries waste, such as nets, rope, and large containers, dominated in mass (87%), and general plastics, such as packaging and plastic articles, dominated in abundance (80%). Fisheries-related debris points to local sea-based sources from vessels operating in the Arctic and nearby. General plastics could point to both land- and ship based sources, as household items are also used on ships and debris can be transported to the north via the oceans current. Overall, 1% of the items (206 out of 14,707 pieces) collected in two big packs (2017 and 2021), bore imprints or labels allowing an analysis of their origin. If the categories ‘global’ and ‘English language’ were excluded, most of identifiable items originated from Arctic states (65%), especially from Russia (32%) and Norway (16%). But almost a third of the items (30%) was of European provenance, especially from Germany (8%). Five percent originated from more distant sources (e.g. USA, China, Korea, Brazil). Global measures such as an efficient and legally binding plastic treaty with improved upstream measures and waste management are urgently needed, to lower the amount of plastic entering our environments and in turn lifting the pressure on the Arctic region and its sensitive biota.